Successful management of COVID-19 induced acute respiratory distress syndrome by extracorporeal membrane oxygenation with 1-year follow-up: A case report. (2021) - Chang, Ko-Wei; Lee, Kuang-Tso; Lo, Yu-Lun; Hu, Han-Chung; Yang, Cheng-Ta; Lin, Shu-Min
Abstract: Coronavirus 2019 (referred to as COVID-19) has infected millions of people throughout the world. This paper reports on a case of COVID-19-induced acute respiratory distress syndrome (ARDS) in which the patient was administered extracorporeal membrane oxygenation (ECMO) to deal with refractory hypoxia. The patient recovered from ARDS following ECMO treatment. In 1-year follow-up, the muscle weakness persisted, and the pulmonary vital capacity recovered sooner than diffusion capacity.